Patterns of coronary heart disease mortality over the 20th century in England and Wales: Possible plateaus in the rate of decline - O'Flaherty Martin; Scarborough Peter; Allender Steven; Capewell Simon (BMC, 2008)
Abstract Background Coronary heart disease (CHD) rates in England and Wales between 1950 and 2005 were high and reasonably steady until the mid 1970s, when they began to fall. Recent work suggests that the rate of change in some groups has begun to decrease and may be starting to plateau or even reverse. Methods Data for all deaths between 1931 and 2005 in England and Wales were grouped by year, sex, age at death and contemporaneous ICD code for CHD as cause of death. CHD mortality rates by calendar year and birth cohort were produced for both sexes and rates of change were examined. Results The pattern of increased burden of CHD mortality within older age groups has only recently emerged in men, whereas it has been established in women for far longer. CHD mortality rates among younger people showed little variation by birth cohort. For younger women (49 and under), the rate of change in CHD mortality has reversed in the last 20 years, indicating a future plateau and possible reversal of previous improvement in CHD mortality rates. Among younger men the rate of change in CHD mortality has been consistent for the past 15 years indicating that rates in this group have continued to fall steadily. Conclusion Although CHD mortality rates continue to drop in older age groups the actual burden of coronary heart disease is increasing due to the ageing of the population. The rate of improvement in CHD mortality appears to be beginning to decline and may even be reversing among younger women.